Policy Bureaucracy - Edward C Page, Bill Jenkins (Oxford University Press, 2005)
‘Actually, childbirth got quite stressful’, said the tall, slim man in his thirties, dressed in a smart grey suit, ‘it was just me and I was given all this responsibility’. He was referring to a job he had looking after a particular aspect of health care policy rather than any physiological miracle. Policymaking is often assumed to involve activism, advocacy, and asserting preferences in the cut and thrust of politics. Yet it also brings with it the active participation of people whose main connection with the policy in question owes little to any normative, still less emotional, attachment to the issue. Many people are involved in policymaking because particular policy responsibilities have been assigned to them as part of their bureaucratic jobs. Such people may be, in fact almost invariably are, extremely interested in their work, and are able to take great pride in what they achieve and to bring professionalism and enthusiasm to it. But they are simply not policy activists, and neither would one want them to be.